1998
DOI: 10.1080/016502598384397
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Perspectives on Coping with the Holocaust Experience: An Attachment Perspective for Understanding the Developmental Sequelae of Trauma across Generations

Abstract: In this paper, we advance a new approach to the intergenerational transmission of Holocaust experiences, by focusing on attachment theory. The approach is used as a framework for interpretation of the results of three studies on Holocaust survivors and their offspring, from different countries (The Netherlands, Canada, and Israel), and based on different conceptual approaches and methods of data collection (quantitative as well as qualitative).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(148 citation statements)
references
References 41 publications
2
141
0
5
Order By: Relevance
“…For example, adult witnesses reported how persecuted infants and toddlers ''knew'' not to move or to make any noise when their hiding place was searched by the Nazis, even when they were hidden under the floor, under layers of blankets, or in dark cupboards (Evers-Emden, 1994;Kestenberg & Brenner, 1996). However, child survivors who had to passively endure exposure to everchanging dangers, may have developed a weak sense of coherence and as a consequence might have become more vulnerable to posttraumatic stress symptoms (Bar-On et al, 1998;Van der Hal & Brom, 2007). A lack of options to participate in shaping outcomes was identified by Keilson (1992) as a cumulative traumatizing experience, as when, for example, during the post-Holocaust era war orphans became the victims of disputed guardianships and of decisions on their upbringing that were not always in their best interest.…”
Section: Discussionmentioning
confidence: 98%
“…For example, adult witnesses reported how persecuted infants and toddlers ''knew'' not to move or to make any noise when their hiding place was searched by the Nazis, even when they were hidden under the floor, under layers of blankets, or in dark cupboards (Evers-Emden, 1994;Kestenberg & Brenner, 1996). However, child survivors who had to passively endure exposure to everchanging dangers, may have developed a weak sense of coherence and as a consequence might have become more vulnerable to posttraumatic stress symptoms (Bar-On et al, 1998;Van der Hal & Brom, 2007). A lack of options to participate in shaping outcomes was identified by Keilson (1992) as a cumulative traumatizing experience, as when, for example, during the post-Holocaust era war orphans became the victims of disputed guardianships and of decisions on their upbringing that were not always in their best interest.…”
Section: Discussionmentioning
confidence: 98%
“…There is however some evidence that Holocaust survivors formed more anxious and less secure attachment with their children, and especially women survivors with their daughters (Bar-On et al, 1998;Brom, Kfir, & Dasberg, 2001;Sagi-Schwartz et al, 2003). While enmeshed mother-daughter dyads with anxious attachment do not constitute psychopathology, many clinicians and theoreticians of eating disorders have described this family constellation as one that may increase the risk for eating disorders (ED) and particularly for anorexia nervosa (AN; Bruch, 1973Bruch, , 1981Minuchin, Roseman, & Baker, 1988).…”
Section: Introductionmentioning
confidence: 95%
“…For example, some clinical studies stressed the emotional distress transmitted over generations (e.g., Barocas & Barocas, 1973), but other studies failed to detect evidence for the transmission of psychopathology (e.g., Leon et al, 1981). Bar-On et al (1998) suggested that these inconsistencies in findings may relate to study characteristics, such as sampling method, research design, and target population (clinical vs. nonclinical). This suggestion turned out to be relevant also for the findings of the present meta-analysis on Holocaust survivors.…”
Section: The Long-term Consequences Of the Holocaustmentioning
confidence: 99%